Improving mechanical and barrier properties of thermoplastic starch and polysaccharide nanocrystals nanocomposites. (15th January 2020) - González, Kizkitza; Iturriaga, Leire; González, Alba; Eceiza, Arantxa; Gabilondo, Nagore
Graphical abstract: Highlights: TPS films were prepared by extrusion-compression technique. Glycerol, D-isosorbide and 1, 3-pronediol were proposed as plasticizers. Excellent affinity was achieved between D-isosorbide and corn starch. Nanocomposites were prepared adding WSNC and WSNC/CNC. The mechanical properties were specially improved when CNC were used. Abstract: Thermoplastic starch (TPS) films were developed with normal maize starch matrix using glycerol, D-isosorbide and 1, 3-propanediol as plasticizers. Besides, TPS nanocomposite films were prepared incorporating waxy starch nanocrystals (WSNC) and cellulose nanocrystals (CNC) into the normal maize starch matrix plasticized with glycerol. Both TPS films and TPS nanocomposite films were obtained by extrusion/compression method. Their mechanical and barrier properties were analyzed, as well as their viscoelastic behavior. According to the results the TPS films plasticized with D-isosorbide presented the highest transparency and the best mechanical and barrier properties, whereas 1, 3-propanediol was not suitable as it was lost during the thermomechanical processing leading to brittle materials. Glycerol plasticized TPS nanocomposites were developed by incorporating polysaccharide nanocrystals, either WSNC (0, 1, 2.5 and 5 wt%) or 1 wt% of both WSNC/CNC in different proportions, in order to approximate the values to those of D-isosorbide films. The effect of both the type and the content of nanocrystal on the viscoelastic behavior and mechanical and barrier properties were investigated. The results suggested that effective interfacial hydrogen bonding interactions were achieved by extrusion/compression processing, obtaining tensile strength, strain at break and Young's modulus increments higher than 100% for nanocomposites reinforced by only 1 wt% of polysaccharide nanocrystals, both WSNC alone and also combining WSNC/CNC in different ratios.